PRODUCTION OF RAW SILK THAT MEETS THE REQUIREMENTS OF QUALITY CLASSES 4A ACCORDING TO THE CRITERIA OF INTERNATIONAL STANDARDS, FROM LOCAL SILKWORM VARIETIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents the results of research work carried out at the Uzbek Research Institute of Natural Fibers in the field of improving the quality of cocoons from local silkworms, increasing the yield and improving the quality of raw silk that meets the requirements of quality class 4A according to the criteria of international standards. New methods of receiving, transporting, storing and preparing cocoons for unwinding are also presented, ensuring high quality raw silk and reducing the specific consumption of cocoons during their production. The results of industrial testing of new methods in production enterprises are also presented.